2021
DOI: 10.1093/ehjci/jeab128
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive characterization of pleural and pericardial effusions using T1 mapping by magnetic resonance imaging

Abstract: Aims Differentiating exudative from transudative effusions is clinically important and is currently performed via biochemical analysis of invasively obtained samples using Light’s criteria. Diagnostic performance is however limited. Biochemical composition can be measured with T1 mapping using cardiovascular magnetic resonance (CMR) and hence may offer diagnostic utility for assessment of effusions. Methods and results A phan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Estimated GBCA concentration in pericardial fluid at the early timepoint, [Gd]early was (20±9 mmol/mL) and at the late timepoint [Gd]late was (70±28 mmol/mL). ROI size in the volume of pericardial fluid in short-axis and perpendicular slice orientations did not differ (18 [14-27] vs 16 [12][13][14][15][16][17][18][19][20][21][22][23] mm 2 , p=0.49). Resulting normal reference ranges are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Estimated GBCA concentration in pericardial fluid at the early timepoint, [Gd]early was (20±9 mmol/mL) and at the late timepoint [Gd]late was (70±28 mmol/mL). ROI size in the volume of pericardial fluid in short-axis and perpendicular slice orientations did not differ (18 [14-27] vs 16 [12][13][14][15][16][17][18][19][20][21][22][23] mm 2 , p=0.49). Resulting normal reference ranges are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Light´s criteria misclassifies 25% of pleural transudates as exudates [2], and doubts have been raised on whether it is at all feasible to use Light´s criteria for pericardial effusions, as the cut off values were validated for pleural effusions. In a recent study involving native T1 measurements of pleural and pericardial effusions, biochemical data enabling the use of Light´s criteria were available mostly for exudates and the cohort was therefore supplemented with presumed transudates by including patients with pericardial and/or pleural effusions and chronic severe left ventricular systolic dysfunction [13]. The validity of this approach is questionable as several studies have shown that most pericardial effusions are misclassified as exudate by Light's criteria, and most if not all normal pericardial fluid is classified as exudate [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations